Martha stewart's organizing ebook The manual for bringing order to your life, home & routines. - Stewart, Martha (2020)
The ultimate guide to getting your life in order—with hundreds of practical and empowering ideas, projects, and tips—from America's most trusted lifestyle authority. Trust Martha to help you master all things organizing—sorting, purging, tidying, and simplifying your life—with smart solutions and inspiration. Here, she offers her best guidance, methods, and DIY projects for organizing in and around your home. Topics include room-by-room strategies (how to sort office paperwork, when to purge the garage or attic), seasonal advice (when to swap out bedding and clothing, how to put away holiday decorations), and day-by-day or week-by-week plans for projects such as de-cluttering, house cleaning, creating a filing system, overhauling the closet, and more. Martha's indispensable expertise walks you through goal-setting, principles of organizing, useful supplies, and creating systems for ongoing success. A look into Martha's own personal calendars offers a template for scheduling essential tasks. Last, plenty of strategies, how-tos, timelines, and checklists will help you stay organized all year long.